Subjective benign paroxysmal positional vertigo in patients with osteoporosis or migraine - González-Aguado,Rocío (2020)
Abstract Introduction Subjective benign paroxysmal positional vertigo is a form of benign paroxysmal positional vertigo in which during the diagnostic positional maneuvers patients only present vertigo symptoms with no nystagmus. Objective To study the characteristics of subjects with subjective benign paroxysmal positional vertigo. Methods Prospective multicenter case-control study. All patients presenting with vertigo in the Dix-Hallpike test that presented to the participating hospitals were included. The patients were separated into two groups depending on whether nystagmus was present or not. An Epley Maneuver of the affected side was performed. In the follow-up visit, patients were checked to see if nystagmus and vertigo were present. Both groups of patients were compared to assess the success rate of the Epley maneuver and also to compare the presence of 19 variables. Results 259 patients were recruited, of which 64 belonged to the subjective group. Nystagmus was eliminated in 67.2% of the patients with benign paroxysmal positional vertigo. 89.1% of the patients with subjective benign paroxysmal positional vertigo remained unaffected by nystagmus, thus showing a significant difference (p = 0.001). Osteoporosis and migraine were the variables which reached the closest to the significance level. In those patients who were taking vestibular suppressors, the percentage of subjective benign paroxysmal positional vertigo was not significantly higher. Conclusions Subjective benign paroxysmal positional vertigo should be treated using the Epley maneuver. More studies are needed to establish a relationship between osteoporosis, migraine and subjective benign paroxysmal positional vertigo. The use of vestibular suppressants does not affect the detection of nystagmus.